(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The phenomenon of the liberty in Turkic world outlook is considered in the given article, which presents itself as ideological premises of Kazakh philosophy. The accent is given to social-political installation of Turkic society, which brightly denominated in Orhono-Eniseysk inscription and in philosophical outlooks of Balasaguni.